Internalisasi Nilai-Nilai Toleransi Melalui Pendidikan Multikultural Terhadap Kelas VI Di SD Penerus Bangsa - Rachmat Yuwono; Naufal Habibie (Jurnal Pendidikan Sosial Dan Konseling, 2023)
Tolerance is a character value that respects diversity and pluralism. Tolerance needs to be instilled from elementary school age because at that age children are sensitive to the differences that exist in themselves and others so they need to be given an understanding regarding how to respect and respond to these differences. The purpose of writing this paper is to discuss tolerance integration strategies that can be carried out through learning and habituation in inclusive elementary schools through multicultural education. Inclusive primary schools are far more vulnerable to differences between students because they place normal students with students with special needs in one class. These conditions make it possible for interventions for children with special needs. By integrating the value of tolerance, students in inclusive elementary schools do not just learn to tolerate differences in ethnicity, religion, race and language, but students learn to respect all forms of deficiencies of students with children with special needs. One alternative to support the inculcation of the character of tolerance within inclusive elementary schools is through multicultural based learning. Multicultural-based learning directs students to view and be tolerant of all forms of differences, be it ethnicity, race, religion, ethnicity, and language, including differences in students with special needs.